2007
DOI: 10.1007/s11606-007-0409-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-Confidence in and Perceived Utility of the Physical Examination: A Comparison of Medical Students, Residents, and Faculty Internists

Abstract: BACKGROUND AND OBJECTIVES:Little is known about the differences in attitudes of medical students, Internal Medicine residents, and faculty Internists toward the physical examination. We sought to investigate these groups' self-confidence in and perceived utility of physical examination skills. DESIGN AND PARTICIPANTS:Cross-sectional survey of third-and fourth-year medical students, Internal Medicine residents, and faculty Internists at an academic teaching hospital. MEASUREMENTS:Using a 5-point Likert-type sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 33 publications
2
51
0
1
Order By: Relevance
“…Clinical assessment of this gland is poorly performed in medical practice, so much so that Wu et al 27 Regarding breast examination, it was reported that only 5.26% of the students performed this exam, and even so only partially, before the intervention with the guide. After the training, this rate increased to 68.42%, but there was still a low percentage of assessments considered complete (36.84%).…”
Section: Salomão Georges Kahwage Neto Et Almentioning
confidence: 99%
“…Clinical assessment of this gland is poorly performed in medical practice, so much so that Wu et al 27 Regarding breast examination, it was reported that only 5.26% of the students performed this exam, and even so only partially, before the intervention with the guide. After the training, this rate increased to 68.42%, but there was still a low percentage of assessments considered complete (36.84%).…”
Section: Salomão Georges Kahwage Neto Et Almentioning
confidence: 99%
“…O exame da tireoide passou de 0% para 61,29% de avaliações completas. A avaliação clínica desta glândula é pouco realizada na prática médica, tanto que Wu et al 27 , em 2007, encontraram um nível de autoconfiança de 2,8 (escala de 1 a 5, sendo 1 o menor nível de confiança) entre os estudantes de Medicina na detecção de um nódulo na tireoide. Porém, com simples intervenções, este cenário é passível de mudança, como foi visto no presente estudo e no trabalho de Haring et al 28 , em 2014.…”
Section: Discussionunclassified
“…Since then, medical students, junior doctors, and general practitioners have consistently reported low levels of confidence in ophthalmoscopy. [4][5][6][7][8] Although some parties have suggested that direct ophthalmoscopy might be replaced by ocular fundus photographs, 3,9 pan-optic ophthalmoscopes 2,10 or by smartphone technology, 11 the reality is that the conventional handheld direct ophthalmoscope remains the most readily accessible tool for fundoscopy to the majority of frontline clinicians. It can be used to quickly and effectively detect a number of lifethreatening and disabling diseases and so remains a diagnostic tool with which all graduating doctors should be familiar.…”
Section: Introductionmentioning
confidence: 99%